2007
DOI: 10.1097/blo.0b013e31805d8606
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminate Pulmonary Nodules in Patients with Sarcoma Affect Survival

Abstract: We prospectively studied 331 sarcoma patients treated between April 1999 and December 2004 to see if small, indeterminate pulmonary nodules are of prognostic significance. Seventy-one (21%) had indeterminate pulmonary nodules on initial spiral CCT. Twenty of 71 (28%) patients with indeterminate nodules progressed with metastatic disease. Metastatic disease developed in 18/20 (90%) in the area of the original indeterminate nodule. The presence of tiny (<5 mm) indeterminate nodules was not a prognostic variable,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 8 publications
1
33
3
Order By: Relevance
“…Three prior studies of patients undergoing screening spiral CT exams upon sarcoma diagnosis reported the prevalence of pulmonary nodules <1cm as 17-34%. (4,29,30) We observed pulmonary nodule(s) in 41% of all sarcoma patients and 45% of osteosarcoma patients at the time of diagnosis. This rate is substantially greater than those reported in the prior studies, which we hypothesize may be related to further advances in CT sensitivity in recent years.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Three prior studies of patients undergoing screening spiral CT exams upon sarcoma diagnosis reported the prevalence of pulmonary nodules <1cm as 17-34%. (4,29,30) We observed pulmonary nodule(s) in 41% of all sarcoma patients and 45% of osteosarcoma patients at the time of diagnosis. This rate is substantially greater than those reported in the prior studies, which we hypothesize may be related to further advances in CT sensitivity in recent years.…”
Section: Discussionmentioning
confidence: 79%
“…This study, however, contained primarily (90%) adult subjects, and young patients were not analyzed as a separate subpopulation. 30 Additional studies addressing this topic from varied perspectives have been published in the Radiology and Orthopedic Surgery literature. Some correlate radiological and surgical or pathological findings 1,3,31 while others evaluate the use of CT scan compared to other modalities, 29, 32 however, variations in age range, nodule definition, and outcome measures make comparison between these data challenging.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the clinicians can now follow-up the patients' disease course without any subsequent intervention, if the size of the pulmonary nodules does not exceed 5 mm without any obvious progression in the number and/or size for 6 months. Rissing [16] involving 331 sarcoma patients, also demonstrated that the presence of nodules which did not exceed 5 mm was not a prognostic variable.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found a false-positive rate of 30% in abdomen and pelvis CT in soft-tissue sarcoma surveillance with a high rate of invasive procedures and subsequent advanced-imaging studies [8]. We should critically analyze existing data to establish a risk-benefit profile of advanced imaging techniques and develop specific chest surveillance imaging guidelines and recommendations for evaluation of subcentimeter pulmonary nodules [7]. As the global utilization of CT scans continues to increase, so will the number of incidentally found pulmonary nodules [5,7].…”
mentioning
confidence: 99%
“…We should critically analyze existing data to establish a risk-benefit profile of advanced imaging techniques and develop specific chest surveillance imaging guidelines and recommendations for evaluation of subcentimeter pulmonary nodules [7]. As the global utilization of CT scans continues to increase, so will the number of incidentally found pulmonary nodules [5,7]. Can we say it is best practice to repeat scans every 3, 6, or 12 months?…”
mentioning
confidence: 99%